The Limits of Targeted Killing in Counterterrorism Operations: An International Law Perspective - Sang YK, Brian (Strathmore Law Journal, 2017)
Despite criticism of targeted killing of suspected terrorists, states continue to justify extensive bases for lethal-force responses to terrorism by arguing that rigid adherence to prescriptive law cannot always be observed in the context of clear and present danger. But, while seemingly cogent, this view wrongly presumes the mutual exclusivity of security considerations and the imperatives of law. It risks exceeding the limits of permissible use of lethal force prescribed in conventional and customary international law. A contrary and more balanced view is advanced in this article. It argues that current international law protecting individuals against intentional killing offers sufficient and practicable guidance for states confronting terrorism. Systematic legal criteria are thus expounded to clarify the legality and admissible limits of targeted killing of suspected terrorists in three contexts: law enforcement, self-defence and armed conflict. With reference to treaties, policy documents and state practice, the article critically examines the preconditions for lawful state-sanctioned killings in counter-terrorist operations. It also identifies the legal challenges and policy implications of resorting to targeted killing. Using comparative case law and operational practice, a legal basis is offered on which Kenya and other nations can effectively tackle the spectre of terrorism within the fair strictures of the law. Every struggle of the state – against terrorism or any other enemy – is conducted according to rules and law. There is always law which the state must comply with.